The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/chem.202100601
|View full text |Cite
|
Sign up to set email alerts
|

The Unusual Photochromic and Hydrochromic Switching Behavior of Cellulose‐Embedded 1,8‐Naphthalimide‐Viologen Derivatives in the Solid‐State

Abstract: Stimuli-responsive chromic materials such as photochromics, hydrochromics, thermochromics, and electrochromics have a long history of capturing the attention of scientists due to their potential industrial applications and novelty in popular culture. However, hybrid chromic materials that combine two or more stimuli-triggered color changing properties are not so well known. Herein, we report a design strategy that has led to a series of emissive 1,8-naphthalimide-viologen dyads which exhibit unusual dual photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 111 publications
1
12
0
Order By: Relevance
“…The current of the TPE-4Py/PAA membrane was recorded at constant voltage under humidification/dehumidification cycles to characterize its response time (Figure e), as the resistance of the membrane dropped with the ionization of PAA and the formation of 4H-TPE-4Py 4+ under high RHs. The results showed that the TPE-4Py/PAA fiber membrane rapidly responded to moisture in 0.82 s and recovered in 2.24 s, which was consistent with the real-time photo records (Figure e, Figure S13), and the response rate was much higher than that of other humidity-responsive color-changing materials. ,, Finally, to confirm the moisture specificity of the fluorescence of the TPE-4Py/PAA fiber membrane, we utilized various vapors of common solvents for comparison, and all of them were unable to induce a change in the fluorescence color and intensity with the exception of water vapor (Figure f, g).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The current of the TPE-4Py/PAA membrane was recorded at constant voltage under humidification/dehumidification cycles to characterize its response time (Figure e), as the resistance of the membrane dropped with the ionization of PAA and the formation of 4H-TPE-4Py 4+ under high RHs. The results showed that the TPE-4Py/PAA fiber membrane rapidly responded to moisture in 0.82 s and recovered in 2.24 s, which was consistent with the real-time photo records (Figure e, Figure S13), and the response rate was much higher than that of other humidity-responsive color-changing materials. ,, Finally, to confirm the moisture specificity of the fluorescence of the TPE-4Py/PAA fiber membrane, we utilized various vapors of common solvents for comparison, and all of them were unable to induce a change in the fluorescence color and intensity with the exception of water vapor (Figure f, g).…”
Section: Resultssupporting
confidence: 74%
“…The results showed that the TPE-4Py/PAA fiber membrane rapidly responded to moisture in 0.82 s and recovered in 2.24 s, which was consistent with the real-time photo records (Figure 4e, Figure S13), and the response rate was much higher than that of other humidity-responsive color-changing materials. 11,12,57 Finally, to confirm the moisture specificity of the fluorescence of the TPE-4Py/PAA fiber membrane, we utilized various vapors of common solvents for comparison, and all of them were unable to induce a change in the fluorescence color and intensity with the exception of water vapor (Figure 4f, g).…”
Section: Performance and Applicationmentioning
confidence: 99%
“…In previous studies, water has been found to decelerate the photoreduction of solid viologens by forming a hydrated viologen–halogen ion pair. 60 In this experiment, films made of hydrophilic polymers could absorb water vapor. The coloration–decoloration processes of the films were investigated under different humidity levels (8% RH, 33% RH, 57% RH, 86% RH and 100% RH).…”
Section: Resultsmentioning
confidence: 98%
“…Stimuli-responsive chromic materials (Yang et al 2018;Jia et al 2021;Liu et al 2021;Samanta et al 2021) such as photochromic, (Qi et al 2021;Yang et al 2021) hydrochromic, (Si et al 2021;Sun et al 2021) thermochromic, (Zhang et al 2020;Kim et al 2021) and electrochromic (Kim et al 2010;Nguyen et al 2021) that exhibit a colorimetric response to external stimuli are extensively investigated due to their novelty in popular culture and potential applications. (Eoh et al 2021;Ma et al 2021;Si et al 2021) Of the stimuli-responsive chromic materials, the hydrochromic materials, (Mishra and Singh 2021) which undergo colorimetric transitions upon interaction with humidity or water, have been widely used for monitoring atmospheric humidity (Park et al 2016a;Bilgin and Backhaus 2020) and shows important applications in sensors, (Sheng et al 2014;Park et al 2016a, b;Bilgin and Backhaus 2020) environmental monitoring, (Zhou et al 2021) displays (Sheng et al 2014;Ju et al 2020) and anticounterfeiting encryption (Ju et al 2020;Yu et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…(You et al 2017;Hong et al 2018) Compared with thermochromic, electrochromic, and photochromic strategies, hydrochromic materials are easy to authenticate by the naked eye without external instruments. Hydrochromic materials have a broad spectrum of applications, (Park et al 2016b;Ni et al 2019) such as breath detection, air humidity detection, (Zhou et al 2021) anticounterfeiting encryption inks, (Kou et al 2018) water content sensors, (Karimipour et al 2020;Sun et al 2021) rewritable papers (Mao et al 2021), and human sweat pore mapping technologies. (Kitamura et al 2018) Hydrochromic materials include graphene oxide, (Chi et al 2021) triarylmethane proton transfer, (Jiang et al 2021) metal salt with crystal water, photonic crystals (PCs), (Jung et al 2021) polydiacetylenes (PDAs), cholesteric liquid crystals, (Stumpel et al 2015;Meng et al 2020;Momtaz and Chen 2020;Yoo et al 2020) lanthanide-ion-coordinated supramolecular hydrogel (Yao et al 2020), aggregation-induced-emission (AIE) molecular, (Jiang et al 2021) and covalent organic framework (Kitamura et al 2018).…”
Section: Introductionmentioning
confidence: 99%